Molecular characterization of Hemibagrus nemurus gonadotropin subunits: cDNA cloning and phylogenetic analysis - Zulperi, Zarirah; Md Yasin, Ina-Salwany; Christianus, Annie; Md Yusoff, Fatimah; Harmin, Sharr Azni (Research in Biotechnology, 2015)
Hemibagrus nemurus is a valuable cultured catfish, but the production is limited due to problems associated with its reproduction, which are controlled by two pituitary gonadotropin (GtH) hormones, follicle-stimulating hormone (FSH) and luteinizing hormone (LH). This study reports the cloning, sequence analysis, and phylogenetic study of GtH subunits from H. nemurus. This work revealed that the cDNAs of Gp-Î±, FSHÎ² and LHÎ² were 656, 728, and 602 nucleotides in length and encoded for mature peptides of 92, 117, and 115 amino acids, respectively. The amino acid sequence identities of H. nemurus mature subunits Gp-Î±, FSHÎ² and LHÎ² in comparison with other fishes were 51-100%, 23-89% and 44-88%, respectively; while in comparison with tetrapods were 64-73%, 12-30% and 26-52%, respectively. The cysteine residues of the mature protein were conserved in comparison with other fishes, which were 10, 13 and 12 cysteines in Gp-Î±, FSHÎ² and LHÎ², respectively. Meanwhile, all potential N-linked glycosylation sites were fully conserved with other vertebrates.Â The Gp-Î±, FSHÎ² and LHÎ² of H. nemurus resembled most to those of Siluriformes, Cypriniformes, and Angulliformes implying a close phylogenetic relationship. This study demonstrates that Malaysian H. nemurus can be utilized as a good model for investigating GtH functions in other catfish species throughout the Indo-Pacific region.